Analisis Anggaran Bahan Baku Pada Project Job Number 2353 pada PT Proserv Batam - Rafika Rusanti (Politeknik Negeri Batam, 2014)
PT Proserv develop a budget material using bottom up method that the budget made by section estimation and planning that existed at PT Proserv Batam located on the proposal, which was submitted to the project manager. Once approved it will be given to the engineering materials with the engineer, the company can surmise how the shape of the project will be done and how much material will be used